Analysis of factors influencing empathy in sports participants using SEM PLS - Muhamad Sazeli Rifki; Anton Komaini; Surya Adi Saputra; Endang Sepdanius; Mert Kurnaz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: This study aims to test relevant predictive models to develop effective interventions related to empathy, sport participation, and culture in sport activities.